Penyesuaian Sosial Remaja Single Sex Schools - Nadia Aulia Nadhirah; Ipah Saripah; Esty Noorbaiti Intani (Indonesian Journal of Educational Counseling, 2020)
ADOLESCENT SOCIAL ADJUSTMENT OF SINGLE SEX SCHOOLS. Teenagers sometimes have the inability to overcome the conflicts they face. This inability can be seen from the behavior of not finding the right ways to overcome problems, resolve demands from the environment, unable to build good relationships with others, hard to believe and be accepted by other people or their environment. The study aims to determine social adjustment in adolescent single sex schools which is a practice of learning by dividing students according to gender, male students are in a classroom with the same sex, and vice versa. The results of evaluations carried out on single sex schools, there are several problems that hinder the task of adolescent development, one of which is the aspect of social adjustment. The study was conducted using a survey method in class XII students of one of the boarding school high schools in Bandung. The results showed 50% of students included in the category of well-adjustment, and 50% of students included in the category of maladjustment. Therefore, it is necessary to formulate an appropriate requirement for guidance and counseling services designed for the development of boarding school students’ self-adjustment.